Canine Visceral Leishmaniasis diagnosis by immunohistochemistry and PCR in skin tissues in association with RIFI and ELISA-test - de Queiroz, Nina M. G. P. [UNESP]; de Assis, Juliana [UNESP]; Oliveira, Trícia M. F. S. [UNESP]; Machado, Rosângela Z. [UNESP]; Nunes, Cáris M. [UNESP]; Starke-Buzetti, Wilma A. [UNESP] (My University, 2010)
The purpose of the present study was to evaluate the immunohistochemistry (IMHC) and PCR (Polymerase Chain Reaction) tests for Canine Visceral Leishmaniasis (CVL) diagnosis and compare the results with serological tests such as the indirect fluorescence antibody test (IFAT), ELISA and a parasitological test (microscopic direct examination of the parasite stained with haematoxylin and eosin - HE). For this study, samples of healthy or lesion skin tissues were obtained from 34 CVL naturally infected dogs classified in three groups: asymptomatic, oligosymptomatic and polisymptomatic. Not only lesion (56.5%) but also healthy skins (31.8%) were positives by IMHC and confirmed by PCR in 97.8% of skin samples. In asymptomatic group, 87.5% dogs were negatives by serological tests, but positives by IMHC in 50% and by PCR in 100%. In oligosymptomatic group, 100%, 85.7% and 28.6% of dogs were positives, respectively by PCR, serological and IMHC tests. In addition, 91.7% of polisymptomatic dogs were serum positive and had intact parasites in the skin. In general, PCR showed higher positivity (100%). The efficiency of each test varied with the evolution of the disease. IMHC may be used to confirm the results of the serology and PCR in inconclusive cases after HE and IMHC. The association of techniques proposed in this study may increase the positivity and contributed to the control of this canine disease.
Diagnóstico da Leishmaniose Visceral canina pelas técnicas de imunoistoquímica e PCR em tecidos cutâneos em associação com a RIFI e ELISA-teste
Keywords: Dogs; Immunohistochemistry; Leishmania; PCR; Skin